Opposite regulation of MDM2 and MDMX expression in acquisition of mesenchymal phenotype in benign and cancer cells - Slabáková, Eva; Kharaishvili, Gvantsa; Smějová, Monika; Pernicová, Zuzana; Suchánková, Tereza; Remšík, Ján; Lerch, Stanislav; Straková, Nicol; Bouchal, Jan; Král, Milan; Culig, Zoran; Kozubík, Alois; et al. (Oncotarget, 2015)
Plasticity of cancer cells, manifested by transitions between epithelial and mesenchymal phenotypes, represents a challenging issue in the treatment of neoplasias. Both epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) are implicated in the processes of metastasis formation and acquisition of stem cell-like properties. Mouse double minute (MDM) 2 and MDMX are important players in cancer progression, as they act as regulators of p53, but their function in EMT and metastasis may be contradictory. Here, we show that the EMT phenotype in multiple cellular models and in clinical prostate and breast cancer samples is associated with a decrease in MDM2 and increase in MDMX expression. Modulation of EMT-accompanying changes in MDM2 expression in benign and transformed prostate epithelial cells influences their migration capacity and sensitivity to docetaxel. Analysis of putative mechanisms of MDM2 expression control demonstrates that in the context of defective p53 function, MDM2 expression is regulated by EMT-inducing transcription factors Slug and Twist. These results provide an alternative context-specific role of MDM2 in EMT, cell migration, metastasis, and therapy resistance.
Keywords: Prostatic Neoplasms; nádory prostaty; myši nahé; Humans; MDM2/MDMX; prostate/breast cancer; epitelo-mezenchymální tranzice; Female; heterografty; Proto-Oncogene Proteins c-mdm2; Phenotype; jaderné proteiny; Mice, Nude; lidé; Cell Cycle Proteins; zvířata; myši; Epithelial-Mesenchymal Transition; protoonkogenní proteiny; Mice; protoonkogenní proteiny c-mdm2; TWIST; transfekce; Breast Neoplasms; ženské pohlaví; Male; fenotyp; Nuclear Proteins; proteiny buněčného cyklu; Proto-Oncogene Proteins; nádorové buněčné linie; nádory prsu; Transfection; Animals; Cell Line, Tumor; Heterografts; epithelial-mesenchymal transition; mužské pohlaví; SNAI2/SLUG